Schooling in Hong Kong : organization, teaching and social context - Postiglione, Gerard A., 1951-; Lee, W. O., 1954- (Hong Kong University Press, 1997)
This volume presents readers with background material for understanding more about the characteristics of Hong Kong education, as well as social and organizational perspectives that will contribute to informed discussion about key educational issues facing Hong Kong educators. The book is organized into three parts. The first part introduces the Hong Kong education system, and its relationship to the labour market, manpower planning and the policymaking process. The second part introduces the organizational and managerial aspects of schools. The third part examines social factors as they affect educational attainment. Here attention is focused upon social stratification, language of instruction and special education. A comprehensive and timely publication, this volume should be of interest to practising teachers and participants in teacher education programmes in Hong Kong.